Conditions relationnelles en contexte de recherche partenariale collaborative - Nathalie Lafranchise; Lyne Kurtzman; Claire Vanier; Maxime Paquet; Kelly Cadec; Berthe Lacharité (Éducation et Socialisation)
Collaboration in a research partnership context is attracting renewed interest. However, this practice of collaboration between researchers and practitioners is not without significant relational challenges. Since these relational challenges are real, it becomes relevant to know the relational characteristics and conditions of collaboration between researchers and practitioners. The purpose of this article is to highlight the relational conditions to be considered in supporting researchers and practitioners in establishing and maintaining satisfactory and successful collaboration. It presents the results of a cross-sectional analysis based on data gathered from three studies highlighting characteristics of the relationship between researchers and practitioners. From this analysis, fourteen relational conditions emerge. They are first described and explained, then put in relation with the elements included in the theoretical framework.